EDUKASI MANAJEMEN KEUANGAN PADA USIA PRA LANSIA DAN LANSIA DI KELURAHAN BAMBU APUS JAKARTA TIMUR - Maya Sova; Sakti Brata Ismaya; Ani Nuraini; Eros Rosmiati; Rushadiyati Rushadiyati; Meiana Harfika (Yayasan Education and Social Center, 2023)
The quality of life of the elderly has several dimensions, namely the dimensions of physical health, psychological, social relationships, environment. On the dimensions of the environment includes sources of income. The problem of sources of income is still many pre-elderly and elderly people who still don't know much about good financial management. Knowledge of financial management is needed to improve the quality of life, especially in the elderly. The Bambu apus village area has several pre-elderly and elderly people who experience a lack of knowledge about financial management. For this reason, it is necessary to provide education to increase knowledge about financial management. The method used in the implementation of community service activities is offline located in the Bambu Apus village with the title Financial management at the age of pre-elderly and elderly in Bambu Apus Village. The implementation of community service activities is carried out by means of material explanations by the urindo community service team. There is an increase in knowledge and understanding in the target age of pre-elderly and elderly. This can be seen from the enthusiasm of the participants and some questions about financial management